Pemanfaatan Botol Plastik Menjadi Pot Tanaman di Kelurahan Joho, Kecamatan Semen, Kabupaten Kediri, Propinsi Jawa Timur - Andajani, Wiwiek; Marwanto, I Gusti Gede Heru; Junaidi; Rachel, Felicia (Kadiri University, 2023)
Inorganic waste is generally difficult to decompose, so that it can pollute the environment. One of the inorganic wastes that can be reused is plastic bottle waste, which can be used as a planting medium. Based on the background of this problem, community service was carried out by involving the community from various representative elements, including LPMD (Empowerment Community Village Institution), PokMas (Group Community), Karang Taruna, PKK (Fostering Family Welfare), and youth from the Joho Village mosque, Semen District, Kediri Regency. The aim of this activity is outreach and education to the public to reduce the production of plastic waste because of its dangers to health and environmental sustainability (reduce principle) and training and direct practice in skills for reusing plastic bottle waste into more valuable goods (reuse principle). The emancipatory participation method was applied to activities so that interaction and dialogue occur with residents through education and training activities with three stages: survey stage, preparation stage, and implementation of education and practical skills training. From this community service activity, it was concluded that education about the dangers of plastic waste for health and environmental sustainability can run well and smoothly. The participants were enthusiastic about participating in the skills training for making plant pots from various waste plastic bottles. Limbah anorganik umumnya sulit terurai sehingga dapat mencemari lingkungan. Salah satu sampah an-organik yang dapat dimanfaatkan kembali (reuse) adalah limbah botol plastik yang dapat digunakan sebagai tempat media tanam. Dari latar belakang permasalahan tersebut, maka pengabdian masyarakat dilaksanakan dengan melibatkan masyarakat dari berbagai unsur perwakilan, di antaranya dari LPMD, PokMas, Karang Taruna, PKK, dan remaja masjid Desa Joho, Kecamatan Semen, Kabupaten Kediri. Adapun tujuan kegiatan ini adalah sosialisasi dan edukasi ke masyarakat untuk mengurangi produksi limbah plastik karena bahayanya bagi kesehatan dan kelestarian lingkungan (prinsip reduce) dan pelatihan dan praktek langsung ketrampilan pemanfaatan kembali limbah botol plastik menjadi barang yang lebih bernilai (prinsip reuse). Metode partisipasi emansipatoris diterapkan pada kegiatan sehingga terjadi interaksi dan dialog dengan warga melalui kegiatan edukasi dan pelatihan dengan tiga tahapan, yaitu: tahap survei, tahap persiapan, dan pelaksanaan edukasi dan pelatihan praktek ketrampilan. Dari kegiatan pengabdian masyarakat ini diperoleh kesimpulan bahwa edukasi tentang bahayanya limbah plastik bagi kesehatan dan kelestarian lingkungan dapat berjalan dengan baik dan lancar. Para peserta antusias dalam mengikuti pelatihan ketrampilan pembuatan pot tanaman dari berbagai limbah botol plastik.